Characterization and Application of Precore/Core‐Related Antigens in Animal Models of Hepatitis B Virus Infection. Issue 1 (23rd July 2021) - Hong, Xupeng; Luckenbaugh, Laurie; Perlman, David; Revill, Peter A.; Wieland, Stefan F.; Menne, Stephan; Hu, Jianming
Abstract : Background and Aims: The hepatitis B core‐related antigen (HBcrAg), a composite antigen of precore/core gene including classical hepatitis B core protein (HBc) and HBeAg and, additionally, the precore‐related antigen PreC, retaining the N‐terminal signal peptide, has emerged as a surrogate marker to monitor the intrahepatic HBV covalently closed circular DNA (cccDNA) and to define meaningful treatment endpoints. Approach and Results: Here, we found that the woodchuck hepatitis virus (WHV) precore/core gene products (i.e., WHV core‐related antigen [WHcrAg]) include the WHV core protein and WHV e antigen (WHeAg) as well as the WHV PreC protein (WPreC) in infected woodchucks. Unlike in HBV infection, WHeAg and WPreC proteins were N‐glycosylated, and no significant amounts of WHV empty virions were detected in WHV‐infected woodchuck serum. WHeAg was the predominant form of WHcrAg, and a positive correlation was found between the serum WHeAg and intrahepatic cccDNA. Both WHeAg and WPreC antigens displayed heterogeneous proteolytic processing at their C‐termini, resulting in multiple species. Analysis of the kinetics of each component of the precore/core‐related antigen, along with serum viral DNA and surface antigens, in HBV‐infected chimpanzees and WHV‐infected woodchucks revealed multiple distinct phases of viral decline during natural resolution and in response to antiviral treatments. A positive correlation was found between HBc and intrahepatic cccDNA but not between HBeAg or HBcrAg and cccDNA in HBV‐infected chimpanzees, suggesting that HBc can be a better marker for intrahepatic cccDNA. Conclusions: In conclusion, careful monitoring of each component of HBcrAg along with other classical markers will help understand intrahepatic viral activities to elucidate natural resolution mechanisms as well as guide antiviral development.